A monument of history in Japanese style, or cognitive synergy of sites, landscpes, crafts and traditions: A trip to the innermost essence of Japan - Affelt, WaldemarJerzy (Protection of Cultural Heritage, 2019)
The Japanese Cultural Agency is implementing the JAPAN HERITAGE project, which will result in a hundred thematic narratives on historical monuments. The applicant and beneficiary is a rural or urban municipality, but the nomination procedure also includes the Prefecture Office. It is stressed that this initiative does not compete with the UNESCO World Heritage List, nor does it introduce a new category of monument, so that there is no need to amend the Act of 30 May 1950 on the Protection of Cultural Property. Strategically, the project aims at social revitalisation by strengthening the sense of identity and intensifying domestic and foreign tourism. Every JAPAN HERITAGE narrative is a branded tourist product, and the tangible and intangible cultural property under legal protection illustrated by it are located in one municipality in the local category, or in many municipalities in a given prefecture, or even in several prefectures - in the collective category. The essence of the project is discussed using the example of narrative 019 ’Date Culture initiated by Masamune’